Osallisuus ja yhteisöllisyys hyvinvointia edistämässä – Taiteen ja kulttuurin vaikuttavuuden arviointi EU-hankkeissa - Honkasalo Marja-Liisa; Laukkanen Anu (Kulttuuripolitiikan tutkimuksen seura r.y., 2022)
The aim of the article is to discuss how the impacts of cultural and artistic activities are discussed, conceptualized and evaluated in the documents of Finnish EU-funded arts and well-being projects. In the documents, artistic activities are claimed to promote social in- clusion, participation and communality. During the last decades, EU has financed hundreds large-scale projects in Finland. For this article, we have analyzed the public documents and reports of three extensive EU-funded art projects.
In the present situation, there are not yet unambiguous evaluation instruments for the impact of art on well-being. The analyzed projects aim at enhancing the well-being of individuals and communities both in work organizations and health and social services. They also aim at preventing social exclusion in everyday life and long term care. In the current Finnish society, profound social, political, economic and cultural changes shape the context for the work of EU projects. First, the projects are seen as a part of a social structural change called projectisation, which is characterized by a new market economy and a gradual decline of the welfare state. Second, the projects are addressed in the context of cultural policy, which currently takes a shape of social policy. Third, the changes for working life are ambiguous. On the one hand, the projects have offered a new field for cultural and art activities, which are used in organizations to improve the well-being of individuals and communities. On the other hand, they also create more surplus value and productivity for the organizations.
On the basis of our analysis, we argue that the effects of arts and culture activities on communality and participation can be viewed as a continuum. In one end of the continuum, communality and participation, which are assisted by the projects’ culture and health activi- ties, may help individuals to get at least a grip on their lives. In the other end, communality and participation are the very conditions for any further effects of arts and culture. In conclusion, we argue that an extensive part of the vagueness in the evaluation is due to the concrete situation of the development projects where they lack methodological training in the evaluation of controversial effects in the interdisciplinary contexts and among multiple public interests.